1993
DOI: 10.1103/physrevb.48.7554
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure analyses ofYBa2Cu3

Abstract: Quantitative structure analyses of YBa2cu, O, s thin films, prepared by radio-frequency sputtering and molecular-beam-epitaxy methods, have been carried out with the x-ray-diffraction method. The expansion in c-lattice parameters of the as-grown thin films were found to be caused by one of the following factors or a combination of them: lattice defects introduced during deposition, deficiency of oxygen, and the disordering of Y and Ba atoms. To study phenomena concerning the deficiency of oxygen, further inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
2
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(47 citation statements)
references
References 26 publications
5
34
2
6
Order By: Relevance
“…In the normal state, a strong anisotropy is present: the resistance in the c-axis direction is ≈100 times larger than in the the b-axis direction just above the superconducting transition, in agreement with earlier reports on untwinned YBCO single crystals [29,30]. The behavior of the resistance with the temperature is also anisotropic: along the b axis, the resistance shows a linear temperature dependence from 300 K down to the superconducting transition, which is typical of optimally doped films [31]; along the c axis, the range of linearity decreases, and a downward bending of the resistance with the temperature, resembling that of an underdoped YBCO c-axis film, develops at low temperatures. Finally, we have recorded a critical temperature T C ≈ 88 K along both the YBCO in-plane directions, calculated as the temperature where the derivative dR/dT is maximum, and a transition broadening T C ≈ 3 K.…”
supporting
confidence: 76%
“…In the normal state, a strong anisotropy is present: the resistance in the c-axis direction is ≈100 times larger than in the the b-axis direction just above the superconducting transition, in agreement with earlier reports on untwinned YBCO single crystals [29,30]. The behavior of the resistance with the temperature is also anisotropic: along the b axis, the resistance shows a linear temperature dependence from 300 K down to the superconducting transition, which is typical of optimally doped films [31]; along the c axis, the range of linearity decreases, and a downward bending of the resistance with the temperature, resembling that of an underdoped YBCO c-axis film, develops at low temperatures. Finally, we have recorded a critical temperature T C ≈ 88 K along both the YBCO in-plane directions, calculated as the temperature where the derivative dR/dT is maximum, and a transition broadening T C ≈ 3 K.…”
supporting
confidence: 76%
“…The dependence of the transition width on oxygen content has been studied by some groups. For example, Ye and Nakamura [24] and Cogollo et al [25] ascribe the broad resistive transitions of the YBCO bolometers to the amount of oxygen deficiency and Uchiyama et al attribute it to nonuniformity of the oxygen content (7 À d) in the YBCO thin film [26]. We investigated the effect of precipitates on the superconducting transition width.…”
Section: Resultsmentioning
confidence: 99%
“…The change in c is mainly caused by the change in d Cu(2)-O(4) because it is much more sensitive to change in the oxygen content than other bond lengths. The lattice parameter c can be easily measured to high precision by diffraction techniques and there has been considerable work [7][8][9][10][11][12] on the relationship between c and the oxygen content of YBCO. However, by examining the data for our single crystals we have found that the dependences of p and c on the oxygen content are not unique: both p and c depend not only on the oxygen content but also on the degree of oxygen ordering in the Cu(1)-O chains.…”
mentioning
confidence: 99%